IMPACT OF PROBLEM LOANS IN COMMERCIAL BANKS IN UZBEKISTAN ON THE COUNTRY’S ECONOMY - Nishanov, Shoazam Bakhramovich; Umbarov, Fakhriddin Tursunovich; Tojiyev, Sardor Dilmurod o‘g‘li (THE INNOVATION ECONOMY, 2026)
This article examines the impact of non-performing loans (NPLs) in commercial banks of Uzbekistan on the national economy. The study analyzes the quality of banks’ loan portfolios, the dynamics of non-performing loans, and their relationship with financial stability and economic growth. Based on official statistical data and international experience, the paper assesses the influence of NPLs on lending activity, investment processes, and the stability of the banking system. The findings provide practical insights for reducing non-performing loans and improving credit risk management mechanisms in commercial banks.